AKIBAT HUKUM KELALAIAN NOTARIS DALAM PEMBUATAN AKTA PPJB: ANALISIS PADA PROSES PERALIHAN HAK MILIK - Tirta Andani; Devanti Vidiasari; Fani Clarais Hungan (Jurnal Ilmiah Advokasi, 2026)
Notarial negligence in drafting a Sale and Purchase Binding Agreement (Perjanjian Pengikatan Jual Beli/PPJB) may lead to significant legal consequences, particularly in the process of transferring ownership rights that do not comply with legal requirements. This study aims to analyze the legal consequences of notarial negligence in the preparation of PPJB, with a case study of Court Decision No. 289/Pdt.G/2023/PN Jkt Brt. This research employs a normative juridical (doctrinal) method using statutory and case approaches, analyzed qualitatively based on applicable legal provisions and judicial reasoning. The findings indicate that the notary committed negligence by drafting a PPJB without a valid prior transfer of rights, which constitutes a violation of the Notary Office Law. Such action fails to fulfill the essential validity requirements of a contract, particularly regarding the certainty of the object. Consequently, the PPJB lacks legal validity and may result in legal uncertainty and potential losses for the parties involved. This study underscores the importance of the notary’s duty of care in exercising professional authority, as well as the need for stricter supervision to ensure legal certainty and protection in the transfer of ownership rights.Keywords: Notarial Negligence, PPJB, Legal Consequences, Transfer of Ownership Rights